If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6x + 3) + -1(-5x + -8) = 3 Reorder the terms: -1(3 + 6x) + -1(-5x + -8) = 3 (3 * -1 + 6x * -1) + -1(-5x + -8) = 3 (-3 + -6x) + -1(-5x + -8) = 3 Reorder the terms: -3 + -6x + -1(-8 + -5x) = 3 -3 + -6x + (-8 * -1 + -5x * -1) = 3 -3 + -6x + (8 + 5x) = 3 Reorder the terms: -3 + 8 + -6x + 5x = 3 Combine like terms: -3 + 8 = 5 5 + -6x + 5x = 3 Combine like terms: -6x + 5x = -1x 5 + -1x = 3 Solving 5 + -1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 3 + -5 -1x = 3 + -5 Combine like terms: 3 + -5 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| (9-x)(3x+5)=0 | | -x-18+2x+4=6x+24 | | a-6b+2c+a-6b+n-2c= | | 9y+3=27 | | 4b+25=9b | | 6(4-1)-5(z+8)=16(z+1) | | y=-(1)-3 | | y=-(0)-3 | | y=-(-1)-3 | | 4b+5x=2x | | -8(t-5)-(t+4)=9 | | 2x+10=27 | | 7.7(-9+2x)=-49 | | y=6(5)-8 | | x=9x-12 | | y=6(1)-8 | | 12(2x-5)=24x+16 | | -(3y+2)-(-2y-8)=5 | | y=6(-1)-8 | | 6+2(x-1)=1-3(x-6) | | 4+6(x-2)=1-5(x-1) | | -49=3x+3x-7 | | -(4y+1)-(-3y-6)=4 | | 12+-2a=2 | | 9ln(8x)=54 | | 2y+10(2)=-16 | | 2y+10(-3)=-16 | | -8+2x-4x=-18 | | -5(3n+2)=10 | | ln(x)+ln(x+4)=0 | | 15y-3=29-y | | 17b-8=0 |